2022
DOI: 10.1136/bcr-2021-245788
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and prolonged cognitive decline as a manifestation of cryptococcal meningitis in a renal transplant patient

Abstract: We report a case of a 67-year-old male recipient of a second renal allograft, presenting with a 9-month history of progressive cognitive and physical decline with features of Parkinsonism. He was HIV-negative. Serum and cerebrospinal fluid (CSF) cryptococcal antigen was positive though CSF culture was sterile. He had progressive deterioration despite induction and consolidation antifungal treatment. Postmortem brain examination confirmed a large burden of yeast forms in the substantia nigra with widespread chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Moreover, we found that infections of C. neoformans and C. gattii induced the degeneration of DA neurons and accelerated aging similarly to the 6-OHDA treatment ( Figure 1C ). These observations have led to the suggestion that invasive cryptococcal infections can induce cellular cytotoxicity and CNS tissue compression leading to the death of DA neurons as seen our present study and in patients with cryptococcal meningoencephalitis associated with prominent features of Parkinsonism ( Wszolek et al., 1988 ; Pedroso and Barsottini, 2012 ; Nelles et al., 2022 ). Therefore, C. elegans can be used as a model to investigate the pathogenesis of cryptococcal infection that induces DA neuronal degeneration related to Parkinsonian symptoms.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, we found that infections of C. neoformans and C. gattii induced the degeneration of DA neurons and accelerated aging similarly to the 6-OHDA treatment ( Figure 1C ). These observations have led to the suggestion that invasive cryptococcal infections can induce cellular cytotoxicity and CNS tissue compression leading to the death of DA neurons as seen our present study and in patients with cryptococcal meningoencephalitis associated with prominent features of Parkinsonism ( Wszolek et al., 1988 ; Pedroso and Barsottini, 2012 ; Nelles et al., 2022 ). Therefore, C. elegans can be used as a model to investigate the pathogenesis of cryptococcal infection that induces DA neuronal degeneration related to Parkinsonian symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Patients with cryptococcal-induced Parkinsonism are often presented with prominent clinical characteristics including bradykinesia, tremor, rigidity, and postural instability. Postmortem brain examination has confirmed the fungal burden located at the substantia nigra and in basal ganglia suggesting the root-cause of Parkinsonism (Wszolek et al, 1988;Pedroso and Barsottini, 2012;Nelles et al, 2022). Degeneration of dopaminergic (DA) neurons of the substantia nigra and a-synucleinopathies are the common denominators of Parkinsonism during aging (Dickson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For CM, studies dedicated to non-human immunodeficiency virus (HIV) patients have further highlighted some of the specific aspects of cryptococcosis in this population, including risk factors associated with neurological involvement [7], the role of plasma and/or cerebrospinal fluid (CSF) cryptococcal antigen (Ag) for prognostic evaluation [8], and the neurological complications of the disease [9]. However, CM outcomes-as well as its clinical features, radiological characteristics, and laboratory findings-have not been analyzed in a large cohort in this particular population [10][11][12].…”
Section: Introductionmentioning
confidence: 99%